Pengaruh Metode Latihan Variasi Smash Terhadap Peningkatan Keterampilan Smash Bolavoli Atlet Di Macan Volly Ball Bengkulu Tengah - Ai Hermini (Educative Sportive, 2026)
This research is motivated by the low smashing ability of volleyball athletes at the Macan Volly Ball club in Central Bengkulu, which is characterized by weak and inaccurate hits. The purpose of this study is to determine the effect of smash variation training methods on improving volleyball smash skills in these athletes. The research method used is quantitative with a pre-experimental design of one-group pretest-posttest design. The population and sample in this study were 15 male athletes of Macan Volly Ball in Central Bengkulu, taken using a total sampling technique. The research instrument used a smashing ability test. The data analysis technique used a normality test and a hypothesis test using a t-test (paired sample t-test). The results showed that the average pre-test score was 19.00 and increased in the post-test to 29.07. The t-test results obtained a t-count value of 11.524 which is greater than the t-table (1.761) with a significance level of $α$ = 0.05. This indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The conclusion of this study is that there is a significant influence of the smash variation training method on improving the volleyball smash skills of athletes at Macan Volly Ball Bengkulu Tengah.